RESISTENSI OBAT PADA PASIEN TUBERKULOSIS PARU DI PUSKESMAS BATU HORPAK KABUPATEN TAPANULI SELATAN - Hutauruk, Dumartina; Situmorang, Manahan; Supartiningsih, Supartiningsih; Sitompul, Hestin Novalina (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Tuberculosis (TB) is an infectious disease with a very high prevalence in several countries in the world. Inadequate TB treatment can cause tuberculosis bacterial resistance to OAT (Anti-Tuberculosis Medicine). The emergence ofresistance M. tuberculosis can be in the form of single drug resistance (DR-TB) or a number or all of the first-line OAT (Multidrug Resistance Tuberculosis). The purpose of this study was to determine drug resistance factors which are influenced by patient habits, medical history, drugs, and health services. This type of research is qualitative research with a case study approach method. There were 6 informants in this study who were two MDR-TB patients, two patient personal monitors, a doctor, and the person in charge of the tuberculosis section. The results showed that the patient had a smoking habit and had a previous history of tuberculosis. In terms of treatment, patients do not routinely take medicines while in health services, the puskesmas have run them well so that there are no mistakes in management. The conclusion of this study is that smoking habits, previous history of tuberculosis disease, and not routine treatment are factors that greatly influence the occurrence of resistance